A Young Child with Sickle Cell Beta Thalassemia: A Case Report and Review of Literatures - Mollah, Md. Abid Hossain; Rahman, Ekhlasur; Islam, Saiful; Morshed, AKM Amirul; Munmun, Farzana Rahman; Shohel, Mohammad (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 245-249 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15368